Sovereignty in Exile : A Saharan Liberation Movement Governs - Wilson, Alice (Philadelphia : University of Pennsylvania Press, 2016)
Sovereignty in Exile explores sovereignty and state power through the case of a liberation movement that set out to make itself into a state. The Sahrawi Arab Democratic Republic (SADR) was founded by the Polisario Front in the wake of Spain's abandonment of its former colony, the disputed Western Sahara. Morocco laid claim to the same territory, and the conflict has locked Polisario and Morocco in a political stalemate that has lasted forty years. Complicating the situation is the fact that Polisario conducts its day-to-day operations in refugee camps near Tindouf, in Algeria, which house most of the Sahrawi exile community. SADR (a partially recognized state) and Polisario (Western Sahara's liberation movement) together form an unusual governing authority, originally premised on the dismantling of a perceived threat to national (Sahrawi) unity: tribes.Drawing on unprecedented long-term research gained by living with Sahrawi refugee families, Alice Wilson examines how tribal social relations are undermined, recycled, and have reemerged as the refugee community negotiates governance, resolves disputes, manages social inequalities, and improvises alternatives to taxation. Wilson trains an ethnographic lens on the creation of administrative categories, legal reforms, aid distribution, marriage practices, local markets, and contested elections within the camps. Tracing social, political, and economic changes among Sahrawi refugees, Sovereignty in Exile reveals the dynamics of a postcolonial liberation movement that has endured for decades in the deserts of North Africa while trying to bring about the revolutionary transformation of a society which identifies with a Bedouin past.
Frontmatter -- Contents -- Introduction: The Social Relations of Sovereignty -- PART I. ASPIRATIONS -- Chapter 1. Hindsight Visions: Tribe and State Power as Projects of Sovereignty -- Chapter 2. Revolutionary Foundations: Unmaking Tribes and Making State Power -- PART II. COMPROMISES -- Chapter 3. Unpopular Law: Tribal, Islamic, and State Law, and the Fall of Popular Justice -- Chapter 4. Tax Evasion: Appropriation and Re distribution Without Tax or Rent -- Chapter 5. Managing Inequalities: Organizing Social Stratification, or Marriage Reinvented -- PART III. DILEMMAS -- Chapter 6. Troubling Markets: Tribes, Gender, and Ambivalent Commodification -- Chapter 7. Party- less Democrats: Electing the Best Candidate or the Biggest Tribe -- Conclusion: Revolution as Moral Contract -- Appendix 1. Notes on Transliteration and Transcription -- Appendix 2. Tribes in Western Sahara -- Notes -- References -- Index -- Acknowledgments
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 13. Sep 2017)
Keywords: National liberation movements -- Western Sahara; Anthropology; Folklore; Human Rights; Law; Linguistics; Political Science